MODUL BELAJAR DAN PEMBELAJARAN UNTUK TOPIK MASALAH-MASALAH DALAM PEMBELAJARAN KIMIA - Gabri E Monica; Diah K Sari; Rodi Edi (Chemistry Education Department of Education and Teaching Faculty, 2021)
Student can’t able to give examples related to the problems of learning chemistry in high school. The purpose of this study is to develop a module of problems in chemistry learning contextual-based in Belajar dan pembelajaran. Development research uses the Rowntree model combined with Tessmer's formative evaluation. The research subjects were 4th semester students participating in Belajar dan Pembelajaran. Data collection techniques carried out through interviews and questionnaires. Data analysis consisted of validation data analysis and student assessment data analysis. Validation data analysis was given to the design expert, pedagogic expert, material expert on a Likert scale and analyzed with Aiken. Analysis of student assessment data is carried out at the one to one and small group stages with the Guttman scale. The results showed the modules developed met the design validation test of 0.87, pedagogical validation of 80, material validation of 0.86 all with a high category. The results of student assessment of modules developed practically where at one to one stage by 90% and small groups by 96.66% with a very high category. It can be concluded that the module of problems in chemistry learning contextual-based in Belajar dan pembelajaran lecture have met the valid and practical criteria.